Bedside Ultrasound of Quadriceps to Predict Rehospitalization and Functional Decline in Hospitalized Elders - Guerreiro, Ana Clara; Tonelli, Ana Claudia; Orzechowski, Roman; Dalla Corte, Roberta Rigo; Moriguchi, Emilio Hideyuki; Mello, Renato Bandeira de (Frontiers in Medicine, 2017)
Objective To evaluate the capacity of total anterior thigh thickness, quadriceps muscle thickness, and quadriceps contractile index, all measured by bedside ultrasound, to predict rehospitalization, functional decline, and death in elderly patients 3 months after hospital discharge. To evaluate intra and interobserver reproducibility of the dominant thigh evaluation method by point of care ultrasound. Methods Cohort study of patients aged 65 years or more admitted to a medium complexity unit in a teaching hospital in southern Brazil. Comprehensive geriatric assessment and ultrasound evaluation of the dominant thigh of each participant were performed. After 3 months of hospital discharge, telephone contact was made to evaluate the outcomes of rehospitalization or death and functional decline—assessed by the 100 points Barthel scale and defined as a decrease of five or more points. Results 100 participants were included. There was no statistically significant difference between intraobserver measurements in the GEE method analysis (p > 0.05), and the mean bias obtained in Bland–Altman plots was close to zero in all four analyses performed, suggesting good intra and interobserver agreement. There was a significant correlation between the echographic measurements (quadriceps thickness and contractile index) and gait speed, timed up and go, and handgrip tests. There was a significant association between contractile index (quadriceps thickness over total anterior thigh thickness multiplied by 100) lower than 60% and functional decline (relative risk 1.35; CI 95% 1.10–1.65; p = 0.003) as well as between the thickness of the quadriceps and rehospitalization or death, in both individuals with preserved walking capacity and in bedridden elders (relative risk 1.34; CI 95% 1.02–1.75; p = 0.04). Conclusion The ultrasonographic method to evaluate thigh thickness was easily applicable and reproducible. The thickness of the quadriceps could predict rehospitalization or death, even in those patients without walking capacity—unable to perform gait speed and timed up and go tests. Additionally, the contractile index was associated with functional decline after 3 months of hospital discharge. This is a promising result, which highlights the bedside ultrasound of the quadriceps as a potential tool for the prognosis evaluation of bedridden hospitalized elderly patients.